Dampak Jangka Panjang Penggunaan AI Terhadap Penurunan Kemampuan Retensi Memori dan Daya Analisis Konvensional Mahasiswa - Sufi Nur Fadillah; Arsya Cindy Amggraeny; Eka Louisza; Tan Evan Tandiyono (Green Publisher Indonesia, 2026)
The rapid development of Artificial Intelligence (AI) has significantly transformed students’ learning processes by providing instant access to information, automated content generation, and academic assistance. While AI enhances efficiency and productivity in completing academic tasks, excessive reliance on these technologies may negatively affect students’ cognitive abilities. This article aims to examine the long-term impact of AI usage on memory retention and conventional analytical skills among university students. The study is based on an analysis of AI usage patterns among Generation Z students and is linked to the concepts of cognitive offloading, digital amnesia, and technological dependency. The findings indicate that continuous dependence on AI reduces students’ tendency to process and retain information independently, diminishes deep engagement with academic literature, and weakens critical and analytical thinking skills. Furthermore, students increasingly rely on AI for problem-solving activities, resulting in a decline in conventional analytical abilities developed through active learning and intellectual effort. Consequently, a balanced and responsible use of AI is essential to ensure that technological convenience does not undermine students’ cognitive development and intellectual independence in the long term